Extensions 1→N→G→Q→1 with N=C22×3- 1+2 and Q=C22

Direct product G=N×Q with N=C22×3- 1+2 and Q=C22
C24×3- 1+2144C2^4xES-(3,1)432,564

Semidirect products G=N:Q with N=C22×3- 1+2 and Q=C22
extensionφ:Q→Out NdρLabelID
(C22×3- 1+2)⋊C22 = D4×C9⋊C6φ: C22/C1C22 ⊆ Out C22×3- 1+23612+(C2^2xES-(3,1)):C2^2432,362
(C22×3- 1+2)⋊2C22 = C2×Dic9⋊C6φ: C22/C2C2 ⊆ Out C22×3- 1+272(C2^2xES-(3,1)):2C2^2432,379
(C22×3- 1+2)⋊3C22 = C23×C9⋊C6φ: C22/C2C2 ⊆ Out C22×3- 1+272(C2^2xES-(3,1)):3C2^2432,559
(C22×3- 1+2)⋊4C22 = C2×D4×3- 1+2φ: C22/C2C2 ⊆ Out C22×3- 1+272(C2^2xES-(3,1)):4C2^2432,405

Non-split extensions G=N.Q with N=C22×3- 1+2 and Q=C22
extensionφ:Q→Out NdρLabelID
(C22×3- 1+2).C22 = Dic182C6φ: C22/C1C22 ⊆ Out C22×3- 1+27212-(C2^2xES-(3,1)).C2^2432,363
(C22×3- 1+2).2C22 = C4×C9⋊C12φ: C22/C2C2 ⊆ Out C22×3- 1+2144(C2^2xES-(3,1)).2C2^2432,144
(C22×3- 1+2).3C22 = Dic9⋊C12φ: C22/C2C2 ⊆ Out C22×3- 1+2144(C2^2xES-(3,1)).3C2^2432,145
(C22×3- 1+2).4C22 = C36⋊C12φ: C22/C2C2 ⊆ Out C22×3- 1+2144(C2^2xES-(3,1)).4C2^2432,146
(C22×3- 1+2).5C22 = D18⋊C12φ: C22/C2C2 ⊆ Out C22×3- 1+272(C2^2xES-(3,1)).5C2^2432,147
(C22×3- 1+2).6C22 = C62.27D6φ: C22/C2C2 ⊆ Out C22×3- 1+272(C2^2xES-(3,1)).6C2^2432,167
(C22×3- 1+2).7C22 = C2×C36.C6φ: C22/C2C2 ⊆ Out C22×3- 1+2144(C2^2xES-(3,1)).7C2^2432,352
(C22×3- 1+2).8C22 = C2×C4×C9⋊C6φ: C22/C2C2 ⊆ Out C22×3- 1+272(C2^2xES-(3,1)).8C2^2432,353
(C22×3- 1+2).9C22 = C2×D36⋊C3φ: C22/C2C2 ⊆ Out C22×3- 1+272(C2^2xES-(3,1)).9C2^2432,354
(C22×3- 1+2).10C22 = D366C6φ: C22/C2C2 ⊆ Out C22×3- 1+2726(C2^2xES-(3,1)).10C2^2432,355
(C22×3- 1+2).11C22 = C22×C9⋊C12φ: C22/C2C2 ⊆ Out C22×3- 1+2144(C2^2xES-(3,1)).11C2^2432,378
(C22×3- 1+2).12C22 = C4○D4×3- 1+2φ: C22/C2C2 ⊆ Out C22×3- 1+2726(C2^2xES-(3,1)).12C2^2432,411
(C22×3- 1+2).13C22 = C42×3- 1+2φ: trivial image144(C2^2xES-(3,1)).13C2^2432,202
(C22×3- 1+2).14C22 = C22⋊C4×3- 1+2φ: trivial image72(C2^2xES-(3,1)).14C2^2432,205
(C22×3- 1+2).15C22 = C4⋊C4×3- 1+2φ: trivial image144(C2^2xES-(3,1)).15C2^2432,208
(C22×3- 1+2).16C22 = C22×C4×3- 1+2φ: trivial image144(C2^2xES-(3,1)).16C2^2432,402
(C22×3- 1+2).17C22 = C2×Q8×3- 1+2φ: trivial image144(C2^2xES-(3,1)).17C2^2432,408